Comparison of PET and fMRI activation patterns during declarative memory processes - Mottaghy, F. M.; Krause, B. J.; Schmidt, D.; Hautzel, H.; Herzog, H.; Shah, N. J.; Halsband, U.; Müller-Gärtner, H.-W. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: In this study neuronal correlates of encoding and retrieval in paired association learning were compared using two different neuroimaging methods: positron emission tomography (PET) and functional magnetic resonance imaging (fMRI). Methods: 6 right-handed normal male volunteers took part in the study. Each subject underwent six 0-15-butanol PET scans and an fMRI study comprising four single epochs on a different day. The subjects had to learn and retrieve 12 word pairs which were visually presented (highly imaginable words, not semantically related). Results: Mean recall accuracy was 93% in the PET as well as in the fMRI experiment. During encoding and retrieval we found anterior cingulate cortex activation, and bilateral prefrontal cortex activation in both imaging modalities. Furthermore, we demonstrate the importance of the precuneus in episodic memory. With PET the results demonstrate frontopolar activations whereas fMRI fails to show activations in this area probably due to susceptibility artifacts. In fMRI we found additionally parahippocampal activation and due to the whole-brain coverage cerebellar activation during encoding. The distance between the center-of-mass activations in both modalities was 7.2 ± 6.5 mm. Conclusion: There is a preponderance of commonalities in the activation patterns yielded with fMRI and PET. However, there are also important differences. The decision to choose one or the other neuroimaging modality should among other aspects depend on the study design (single subject vs. group study) and the task of interest.
Keywords: PET; fMRI; declarative memory; paired word associations